Exploring the clinical roles of nurses in the rehabilitation of acute stroke patients at private hospitals in Cape Town, South Africa - Mhango, Ethel Chimango (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCur)--Stellenbosch University, 2018.